Phylogenetic Systematics in educational journals (Research, Society and Development, 2022)
Systematics is the science that includes Taxonomy, in turn responsible for describing, naming, identifying and classifying living beings. Systematics is important in organizing information about all the biological diversity present on the planet. Classification systems gained a new dimension from Phylogenetic Systematics, which currently brings the most appropriate form for the classification of living beings, that is, ancestry. The present work was developed from the discipline of Phylogenetic Systematics, offered in the Graduate Program in Science and Mathematics Education, with the objective of collecting articles on Phylogenetic Systematics existing in national and international journals in the area of Science Teaching. Thirteen articles were found, however, only those that address Phylogenetic Systematics related to Science Teaching issues were analyzed. Of all the studies found, 50% performed textbook analysis, and few brought phylogeny as an integrating axis in the study of living beings. From the analysis of the articles we can see that Phylogeny as an evolutionary process has been little worked in Science and Biology Teaching, as the books still insist on the functional approach, bringing only physiological aspects when dealing with different groups of living beings. In addition, there is a need to encourage discussions on phylogeny in the process of initial teacher education.